Increasing the usage of demand-response transit in rural Kansas - Geiger, Brian Christopher (Kansas State University, 2009)
Public transportation in rural America has existed for decades. Its providers are challenged with low populations and long distances in rural areas. Many of these rural transit providers have been in existence for many years, but ridership still remains low. These providers usually operate in a demand-response format, as opposed to large cities, where buses run on fixed routes. This research was conducted to see if any type of service improvements or enhancements could be found in order to increase ridership of demand-response transit service in rural Kansas. In order to determine if ridership of public transportation in rural Kansas can be increased, customer satisfaction surveys were conducted. One survey was distributed to current riders of demand-response systems, one survey distributed to non-riders of public transportation, and the last survey given to providers to obtain basic system information throughout Kansas. Ridership is significantly skewed toward the elderly, disabled, and those who either choose not to drive or are unable to drive. Those who do not fall into one of these three categories often do not use public transportation in rural areas. For most of the riders, public transportation is their only reliable method of mobility as they are transit dependent. Only 35% of the riders had a personal vehicle they could use to make the trip had public transportation not been available. Riders of demand-response transit systems in rural Kansas are pleased with the service provided as a whole. Non-riders are ambivalent toward demand-response transit service. They appreciate the fact that in many cases general public transportation service exist, but they are also generally unwilling to use it themselves. These are typically choice riders, and are unlikely to switch to demand-response transit due to their other mobility options. It was found that the more vehicles a person has access to in their household, the less knowledge they have about public transportation in their area. These people are content to use the vehicles they have, because it is more convenient than using public transportation in rural Kansas. Improvements to the provider’s system, like extending operating hours and days, along with implementing GIS-assisted scheduling may bring higher ridership. However, this may only increase the number of rides by the same current riders with few new riders grained. Increasing the usage of demand response ridership will continue to be a challenge in the future with the increasing number of elderly in the years to come.
Keywords: Demand-response; Ridership; Rural; Transit; Kansas; Engineering, Civil (0543)